2020
DOI: 10.1039/d0sc00485e
|View full text |Cite
|
Sign up to set email alerts
|

Isolating reactive metal-based species in Metal–Organic Frameworks – viable strategies and opportunities

Abstract: Metal–organic frameworks can be used to stabilise reactive metal-based species, uncover new reactivity, and investigate metal-centred reactions responsible for catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 184 publications
(238 reference statements)
2
59
0
1
Order By: Relevance
“…[44] If MOFs with specific or complex properties are the targets of a given study, then ligand synthesis can become increasingly laborious. However, a number of approaches to preparing specific, complex materials are known, not least of which is post-synthetic modification [45] of the framework which can allow the introduction of sensitive chemical groups -groups which may not withstand the initial MOF synthesis such as metal complexes [46] -to the framework structure.…”
Section: Ease Of Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[44] If MOFs with specific or complex properties are the targets of a given study, then ligand synthesis can become increasingly laborious. However, a number of approaches to preparing specific, complex materials are known, not least of which is post-synthetic modification [45] of the framework which can allow the introduction of sensitive chemical groups -groups which may not withstand the initial MOF synthesis such as metal complexes [46] -to the framework structure.…”
Section: Ease Of Synthesismentioning
confidence: 99%
“…MOFs are known to undergo reversible structural transformations and post synthetic modifications of MOFs is a vast area of research in its own right. [45] In addition to chemical modification of MOFs through the formation of covalent bonds, it is also possible to post-metallate MOFs and this allows the introduction of reactive metal complexes, [46] an approach which facilitates the study of catalytic processes (see Section 8).…”
Section: Structural Transformationsmentioning
confidence: 99%
“… 16 Crucially, metal–organic frameworks can often be prepared in single-crystalline form, which enables structural characterization of the first coordination sphere at reactive metal centers with atomic resolution. Indeed, researchers have harnessed this feature to study unusual metal–ligand binding modes 17 and to structurally elucidate intermediates in catalytic, 18 photoinduced, 19 and cooperative 20 reactions. Along these lines, we have recently shown that four-coordinate metalloporphyrins within the Zr-based framework PCN-224 ( ref.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the formation of MOFs prevents the release of CO2 upon heating. This is along with the previous reports of the stabilization of the thermally unstable linkers in the lattices of MOFs 35,36. The stabilization of carbamate was further studied using density functional theory (DFT) calculations of the bond energy between Zn 2+ and PDC 2− using the a hybrid exchange-correlation functional.…”
mentioning
confidence: 69%